An evaluation of deep eutectic solvents for charge/discharge tests using all-vanadium redox couples for flow batteries / Laleh Bahadori - Laleh, Bahadori (2015)
One of the key constraints limiting the widespread commercialization of redox flow batteries (RFBs) appears to be their low energy density. A mean of overcoming this drawback has been the employment of non-aqueous electrolyte solvents that can offer a wide potential window of operation and increase the energy capacity of the system. In the present study, low cost ionic liquids analogues, namely deep eutectic solvents (DESs), have been proposed as non-aqueous electrolytes for potential application in the RFB. The proposal is based upon diffusion coefficient and electrode rate kinetics data. Different DESs, based on ammonium and phosphunium salts with various hydrogen bond donors (HBDs) including acids, alcohols and amid have been prepared. The evaluation of DESs as new electrolytes demands a perception of their main physicochemical and electrochemical properties. For this purpose, selected properties of the prepared DESs were measured and documented. The DESs were employed as electrolytes to determine the effects of electrode type and solvent on the electrochemical system studied. Two organometallic redox couples, ferrocene/ferrocenium (Fc/Fc+) and cobaltocenium/cobaltocene (Cc+/Cc) were utilized as internal reference redox systems to provide a known and stable reference point in different DESs. Diffusion coefficient (D) of Fc/Fc+ and Cc/Cc+ was found to be of the order of 10-10 to 10-8 cm2 s-1 in all studied DESs, and these values do not change significantly with concentration. The kinetics of the Fc/Fc+ and Cc+/Cc electrochemical systems have been investigated over a temperature range from 298 to 338 K. The standard heterogeneous electron transfer rate constant (k0) was calculated at different temperatures by means of a logarithmic analysis. From the comparison of results, it can be inferred that the D and k0 for ammonium based DES prepared from ethylene glycol HBD was greater than those for other DESs. iv In spite of the importance of DESs and their interesting advantages, their applications in redox flow battery are scarce. The present work is an attempt to describe a single-element non-aqueous redox system based on vanadium (III) acetylacetonate (V(acac)3) in DES, in order to overcome the key technological barriers of developing vanadium redox battery, such as the stability of electrolyte. The solubility of V(acac)3 was determined in selected DESs and the maximum solubility was approximately 0.1 M in the ammonium salt:ethylene glycol DES. Subsequently, the potential application and kinetic behavior of the selected DES were evaluated using cyclic voltammetry. The cyclic voltammetry show that the DES was stable in a functional potential range (-2.12–1.22 V). The D of V(acac)3 in the DESs electrolytes were estimated to be in the range of 0.02–0.69×10-6 cm2 s-1 at room temperature. Charge–discharge performance was determined using a static H-type electrochemical cell and coulombic efficiencies near 50% at 50 % state of charge (SOC) were achieved. The charge/discharge results were very similar to the use of acetonitrile as a solvent. This research will open up new opportunities for evaluating different types of DESs for enhancing the performance of all-vanadium RFB.